Korido-komiks into film sourcing, adapting and recycling the Bernardo Carpio story - Arriola, Joyce L. (2014)
This paper explores the generic transformations resulting from adapting a korido (metrical romance) into a komiks story and into a film. The resulting discourse is an examination of Filipino film adaptation practices as exemplified through the film Bernardo Carpio, a 1951 Sampaguita Pictures production that has been faithful to the Liwayway komiks story authored by novelist Faustino Galauran who freely adapted from the pre-existing korido. The idea of sourcing and adapting is based not only on the premise that an existing text summons immediate acceptance by the viewers but also on the argument that a culture of recycling is in place and allows for certain stories to take on an allegorical implication.
Keywords: Film adaptations; Mythology; Comic books, strips, etc